On the state of the Balarusian healthcare system - Lev Lvovskiy (Global Labour University - Freunde und Förderer e.V., 2024)
The Belarusian healthcare system is a direct heir to the Soviet medical model, retaining all its strengths and weaknesses. Currently, its functioning can be considered satisfactory: key indicators such as life expectancy and healthy life expectancy are generally comparable to European standards. However, the main problem is that the system is not sustainable in the medium and long term. At present, it is relatively inexpensive for taxpayers, but this is achieved through low salaries and challenging working conditions for doctors. Consequently, these factors are leading to the gradual relocation of medical professionals, putting the future of Belarusian healthcare at risk.
Keywords: 330